Outdoor Education in Geography: A Specific Educational Strategy - Svobodová, Hana (Masaryk University Press, 2019)
The publication aims to promote outdoor education as a strong teaching strategy, to describe its links to the school curriculum, and to offer teachers a helping hand in developing the concept of outdoor education. All of this is based on exploring the benefits of outdoor education in teaching and promoting physical activity, which is a natural part of it. The first part of the book analyses how outdoor education is established in the Czech school curriculum, outlining the steps necessary for outdoor education to be implemented, in terms of preparation of both the teachers and pupils. This section also provides recommendations for the development of an outdoor education concept for elementary schools. The second part of the publication is devoted to outdoor education research conducted in cooperation with elementary school teachers, pupils of a model elementary school and their parents, are presented in detail.